2014
DOI: 10.22487/j25805924.2014.v2.i2.3179
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Model Pembelajaran Kooperatif Tipe Numbered Head Together (NHT) Dengan Pendekatan Contextual Teaching And Learning (CTL) Terhadap Hasil Belajar Fisika Siswa Kelas VIII SMP Negeri 2 Balaesang

Abstract: Abstrak - Penelitian ini bertujuan untuk melihat pengaruh model pembelajaran kooperatif tipe numbered head together dengan pendekatan contextual teaching and learning, pada kelas VIII SMP Negeri 2 Balaesang. Jenis penelitian yang digunakan adalah eksperimen kuasi dengan desain “The Non Equivalen Pretest-Posttest Design”. Sampel dipilih dengan menggunakan teknik purposive sampling. Sampel penelitian kelas VIIIA sebagai kelas kontrol dan kelas VIIIB sebagai kelas eksperimen. Instrumen yang digunakan tes hasil be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Nurfaidah, et al, (2011) based on her research concluded that student learning outcomes improved through the application of cooperative learning models of student team achievement division (STAD) types. Karmila, et al, (2014) based on the results of their research concluded that the numbered head together (NHT) type of cooperative learning model with a contextual teaching and learning (CTL) approach can influence student learning outcomes. Pardirla (2013) based on the results of his research concluded that the application of the influence of cooperative learning teams-assisted-individualization type (TAI) affects the learning outcomes of students.…”
Section: Discussionmentioning
confidence: 99%
“…Nurfaidah, et al, (2011) based on her research concluded that student learning outcomes improved through the application of cooperative learning models of student team achievement division (STAD) types. Karmila, et al, (2014) based on the results of their research concluded that the numbered head together (NHT) type of cooperative learning model with a contextual teaching and learning (CTL) approach can influence student learning outcomes. Pardirla (2013) based on the results of his research concluded that the application of the influence of cooperative learning teams-assisted-individualization type (TAI) affects the learning outcomes of students.…”
Section: Discussionmentioning
confidence: 99%
“…Game according to Bettelheim is an activity characterized by the existence of rules that are mutually agreed upon and determined from the outside to carry out an activity that has a purpose (Azizah, 2016). From the opinions that have been stated previously, it can be seen that the game is an activity that has the goal of measuring a child's ability and potential (Widya et al, 2020). Games can be divided into two types, namely traditional games and modern games (Brigita, 2020).…”
Section: Introductionmentioning
confidence: 99%